SINTESIS POLIMER TERCETAK MOLEKUL SUDAN III UNTUK PEMISAHAN DAN ANALISIS DALAM KOSMETIK PERONA PIPI - Utari, Ulvah
Sudan III was a synthetic azo dye. Sudan III was classified as a category 3 carcinogen by the International Agency for Research on Cancer (IARC). The aim of this research was to synthesis a selective molecularly imprinted polymer (MIP) for separation and analysis sudan III in blush on. Synthesis of MIP was prepared by using sudan III as the molecular template, methacrylic acid (MAA) as the functional monomer, ethylene glycol dimethacrylate (EGDMA) as a cross linker, 2.2’- azoisobutyronitrile (AIBN) as the initiator, and chloroform as the porogenic solvent. The imprinting factor (IF) was calculated by comparing the area under the curve of sudan III on the imprinted polymer with a comparable non imprinted polymer (NIP). The template : monomer : crosslinker ratio of 1:4:20 resulted an IF of 2.4039. MIP was characterized by fourier transform infrared (FTIR) and evaluated using equilibrium batch rebinding method. Selectivity test showed that MIP can be used for selective extraction of sudan III spiked with rhodamine B. The recovery for blush on sample which was spiked with sudan III was 83.14% after pretreatment with molecularly imprinted solid phase extraction (MISPE). Analysis method of sudan III with spectrofotometer UV-Visible gave valid result, linearity with r = 0.999 and Vxo = 2.0%, accuracy with recovery = 98.31 –101.33%, and precision with coefficient of variation = 0.69%.